(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Despite the progress in the development of medical and endoscopic methods of treatment, PU surgery with its complicated course remains a subject of interest in terms of developing or improving various options for surgical approaches, the essence of which is aimed at reducing the incidence of various postoperative complications (Nazirov F.G., 2003; Vlasov A.P., 2020; Agaba E.A., 2016; Zhu C, 2021). In this regard, the frequency and spectrum of complications certainly depend both on the surgical technique and on other factors: the type of suture material, the initial condition of patients, and others (Olekseenko V.V., 2017; Hata T., 2014; Kumar P., 2014; Chiarello M.M., 2019; RosaF., 2019).